White Coat: Origins, Composition, Semantics, Pragmatics, and Word-Formation Potential of Russian Phraseological Unit - T. V. Leontyeva (Научный диалог)
This study provides a comprehensive description of the expression ‘white coat,’ along with a linguistic framework that has developed around this idiom. A total of 312 instances of the expression ‘white coat’ were collected through a systematic sampling from online sources, forming the author’s database of examples. Methodologies employed include contextual analysis, semantic-motivational analysis, definitional modeling, and discourse analysis. The author concludes that the idiom ‘white coat’ has formed within Russian linguistic culture unde the influence of several factors: speech practices within comedic (anecdotal) discourse, an internet meme featuring Valeria Novodvorskaya holding a placard (even if one assumes its fake nature), and the systemic linguistic potentials of color designation. It is asserted that the expression ‘white coat’ signifies one of the communicative roles predominantly realized in virtual communication, though not exclusively so. The study demonstrates that the structural-semantic appearance of the expression is variable, along with its grammatical characteristics, for example: ‘[someone] in a white coat’, ‘[someone] without a white coat’, ‘take off the white coat’, etc. (in these instances, the nominal component ‘white coat’ does not denote a person; this represents the initial stage of the expression’s functioning, closely related to the original discursive complex ‘I stand in a white coat’). Furthermore, it is shown that in network discourse, a transformation occurs into an evaluative nomination of a person as ‘the white coat’ (‘I was such a white coat’).